“Open science” meets commercial realities: a qualitative study of factors influencing sharing in synthetic biology research in Australia - McLennan, Alison; Maslen, Sarah (Frontiers in Bioengineering and Biotechnology, 2025)
This paper examines sharing of data and materials in synthetic biology research and the impact of intellectual property regulation and commercialization imperatives. Data-sharing, access to scientific knowledge, ownership of that knowledge and collaboration are critical issues in biotechnology research, as highlighted in the recent COVID-19 pandemic. We present a sociolegal investigation of drivers of sharing and hindrances to these activities in synthetic biology. This field has a particular emphasis on driving innovation through openness and sharing of the building blocks of research, as opposed to using intellectual property (IP) rights to limit access to these. We examine the perspectives and practices of synthetic biologists in both university and commercial settings, as well as commercialization professionals. We argue that synthetic biologists simultaneously manage two sets of imperatives. On the one hand, sharing is driven by cultural norms, pursuit of scientific progress and strategic benefits to the sharer. On the other, synthetic biologists need to protect their scientific careers, preserve the patentability of developments with commercial potential, and manage obligations to commercial partners and institutions. As their careers may not be purely academic or commercial, they need to appreciate the prerogatives of the particular “hat” that they are wearing on a given project, and also form judgments of commercial value, drawing on a distinction between fundamental and applied research.